Rescue strategies for valproic acid overdose poisoning: Case series and literature review - Renzhu Liu; Lu Xiao; Yixiang Hu; Qingzi Yan; Xiang Liu (Clinical Case Reports, 2024)
Key Clinical Message Valproic acid (VPA) is a wide‐ranging anti‐epileptic medication that primarily affects bipolar disorder, mania, and migraine. The leading causes of mortality associated with acute poisoning from VPA are nervous system toxicity, drug‐induced shock due to encephalopathy from hyperammonemia, as well as acute liver and kidney failure, and respiratory depression that contribute to hemodynamic instability. Treatment of acute VPA poisoning primarily involves in vitro elimination methods, including hemoperfusion (HP), hemodialysis, and hemofiltration, as well as drug remedies such as L‐carnitine and meropenem. Nonetheless, there are conflicting opinions regarding drug usage. This article details the three cases of acute poisoning from VPA. The fundamental approach to treatment employs HP assisted by blood concentration monitoring to alleviate shock and stabilize hemodynamics. This investigation presents guidance for the treatment and management of acute poisoning with VPA in clinical settings.